2012
DOI: 10.1007/s00432-012-1258-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased number of regulatory T cells (T-regs) in the peripheral blood of patients with Her-2/neu-positive early breast cancer

Abstract: Increased numbers of circulating T-regs may contribute to the higher metastatic potential of Her-2/neu-positive cells. A potential role as a prognostic or predictive parameter is currently being analyzed in a larger cohort of patients with sufficient follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 36 publications
2
29
0
4
Order By: Relevance
“…In this study, first we focused on breast cancer and examined the percentage of T and B regulatory cells and compared them with healthy individuals. As we expected and similar to the result of other studies [12,29], the breast cancer patients had a significantly elevated percentage of circulating CD4 ? CD25 ?-FoxP3 ?…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, first we focused on breast cancer and examined the percentage of T and B regulatory cells and compared them with healthy individuals. As we expected and similar to the result of other studies [12,29], the breast cancer patients had a significantly elevated percentage of circulating CD4 ? CD25 ?-FoxP3 ?…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown an increased circulating Tregs in HER2 amplified patients [12,29]. In this study, we also observed a significant increase in circulating Tregs of HER2 amplified patients.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Patients and experimental models with cancer showed that Treg cells down-regulated the activity of effector function against tumors, resulting in T-cell dysfunction in cancerbearing hosts (Weiss et al, 2012;Sakuishi et al, 2013). An increased population of Treg cells was reported in patients with ovarian cancer (Wicherek et al, 2011), lung cancer (Erfani et al, 2012), and breast cancer (Decker et al, 2012). However, there are no previous reports describing Treg cells in gastric cancer.…”
Section: Introductionmentioning
confidence: 99%